2011
DOI: 10.1016/j.juro.2011.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cytoskeletal Structure of Smooth Muscle Cells in Ureteropelvic Junction Obstruction

Abstract: We demonstrated activation of apoptosis and a critical alteration of cytoskeleton that might explain the altered function and the increased apoptosis in smooth muscle cells in ureteropelvic junction obstruction. The delayed rearrangement of the cytoskeleton of smooth muscle cells in ureteropelvic junction obstruction might be linked to a postnatal splicing from α7A and β1A to α7B and β1D integrins, respectively. This relationship could explain the common clinical scenario of spontaneous improvement of hydronep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
4
12
0
1
Order By: Relevance
“…Similarly, it has been observed that muscular cells in congenital obstructed uretero-pelvic junction in humans are in an embryonic state as well. In particular, a higher expression of embryonic α7A and β1A isoforms and a lower expression of adult subunit α7B and β1D isoforms were documented in the muscular cells of congenital obstructed uretero-pelvic junction as compared to control specimens [10]. In our study, we tried to investigate the expression of embryonic α7A and β1A and mature α7B and β1D integrins in cremaster muscular cells of patients affected by a congenital undescended testis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, it has been observed that muscular cells in congenital obstructed uretero-pelvic junction in humans are in an embryonic state as well. In particular, a higher expression of embryonic α7A and β1A isoforms and a lower expression of adult subunit α7B and β1D isoforms were documented in the muscular cells of congenital obstructed uretero-pelvic junction as compared to control specimens [10]. In our study, we tried to investigate the expression of embryonic α7A and β1A and mature α7B and β1D integrins in cremaster muscular cells of patients affected by a congenital undescended testis.…”
Section: Discussionmentioning
confidence: 94%
“…Previous findings reported a critical structural impairment of the cytoskeleton at the level of the congenital obstructed uretero-pelvic junction, linked to an abnormal arrangement of integrins [10].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Öte yandan kronik fazda ise, hidronefroz, renal atrofi, böbrek ağırlığında azalma, intertisyel fibrozis ve böbrek fonksiyon bozukluğu gelişmektedir (24) . Deneysel ve klinik çalışmalar (1,3,6,10,16,27,30) ; nefropatiye neden olan başlıca faktörle-rin glomerüler dinamikleri ve tübüler fonksiyonları etkileyen çeşitli vazoaktif peptidler ve bunların neden olduğu apopitotik mekanizmalar olduğunu gös-termiştir.…”
Section: Discussionunclassified
“…Kaya et al showed an overexpression of extracellular matrix proteins and decreased nerve supply in intrinsic UPJ obstruction (3). Cutroneo et al demonstrated an increasing activation of apoptosis and a critical alteration in UPJ obstruction (4).…”
mentioning
confidence: 99%